1988
DOI: 10.1111/j.1471-4159.1988.tb04859.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Homeostasis in Digitonin‐Permeabilized Bovine Chromaffin Cells

Abstract: The regulation of cytosolic calcium was studied in digitonin-permeabilized chromaffin cells. Accumulation of 45Ca2+ by permeabilized cells was measured at various Ca2+ concentrations in the incubation solutions. In the absence of ATP, there was a small (10-15% of total uptake) but significant increase in accumulation of Ca2+ into both the vesicular and nonvesicular pools. In the presence of ATP, the permeabilized cells accumulated Ca2+ into carbonyl cyanide m-chlorophenyl hydrazone (CCCP)-sensitive and -insens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
5
17
1
Order By: Relevance
“…One explanation may be that the digitonin-permeabilized cells lose the ability to take up additional Ca2+. This interpretation is supported by the minute amounts of 45Ca2+ whose release was induced by 1P3 from a nonmitochondrial intracellular compartment in digitonin-permeabilized chromaffin cells (Kao, 1988). In contrast, the present data demonstrate that the IP3-sensitive Ca2+ compartment plays an important role in intracellular Ca2+ signaling and control of exocytosis within chromaffin cells.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…One explanation may be that the digitonin-permeabilized cells lose the ability to take up additional Ca2+. This interpretation is supported by the minute amounts of 45Ca2+ whose release was induced by 1P3 from a nonmitochondrial intracellular compartment in digitonin-permeabilized chromaffin cells (Kao, 1988). In contrast, the present data demonstrate that the IP3-sensitive Ca2+ compartment plays an important role in intracellular Ca2+ signaling and control of exocytosis within chromaffin cells.…”
Section: Resultssupporting
confidence: 72%
“…In digitonin-permeabilized adrenal chromaffin cells, high concentrations of IP3 were required to induce release of Ca2+. Furthermore, a second dose of IP3 failed to induce release of Ca2+, and the Ca2+ released could not be taken up again by the compartment (Stoehr et al, 1986;Kao, 1988). These findings argue against a major contribution of the IP3-sensitive Ca2+ compartment during stimulation of adrenal chromaffin cells.…”
mentioning
confidence: 89%
“…This agrees well with the finding that CCCPsensitive Ca 21 pools become active at above pCa 6 in permeabilized chromaffin cells (14). We also obtained the same results using 1 mM NaN3, another metabolic inhibitor (31) (data not shown).…”
Section: Assays Of Protein and Organelle Markersupporting
confidence: 81%
“…6: a and b). The Ca2+-storing organelles in the adrenal medulla have been studied using the uncoupler CCCP or vanadate (nonselective Ca"-ATPase inhibitor), in digitonin-permeabilized cells (14). In organelles of adrenal chromaffin cells, however, the selectivity of these drugs has not been studied in detail.…”
Section: Assays Of Protein and Organelle Markermentioning
confidence: 99%
“…It has been previously shown that the intracellular nonmitochondrial Ca 2~pool has high affinity and that the Na + /Ca 2+ exchanger has low affinity for handling Ca2~ (Kao, 1988;Kao and Cheung, 1990). The Na~/ Ca2~exchanger is important in removing Ca2~from the cytosol, when the [Ca 2+ I, is increased after stimulation, and therefore controls the time for cessation of secretion.…”
Section: Discussionmentioning
confidence: 99%